The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.14482/zp.22.5832
|View full text |Cite
|
Sign up to set email alerts
|

Formación en el trabajo con familias para la educación de la primera infancia

Abstract: Link to publication Citation for published version (APA):Gómez Rendón, J., & Salazar Proaño, D. (2015). La lengua andwa: una experiencia en documentación y reapropiación lingüística a través de la educación = The andwa language: a case of documentation and linguistic reclamation through education. Zona Proxima, 23, 106-117.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0
9

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
6
9
0
9
Order By: Relevance
“…In order to help themselves understand the meaning of English words, they always asked the meaning of certain English words in Bahasa or certain Indonesian words in English. This result is also correlated with what was found by Ramos (2017) that in learning EFL, visually impaired students are using cognitive strategy, however he found that the activities are practicing, repetition, receiving and sending messages: getting the idea quickly, analyzing and reasoning, creating structure for input and output, summarizing, translating, using L1. It means that the result of this study is quite different from the previous study conducted by Ramos (2017) in which this study only found that the visually impaired students used cognitive strategy, by conducting several activities like practicing, repetition, summarizing, and translating.…”
Section: Findings and Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In order to help themselves understand the meaning of English words, they always asked the meaning of certain English words in Bahasa or certain Indonesian words in English. This result is also correlated with what was found by Ramos (2017) that in learning EFL, visually impaired students are using cognitive strategy, however he found that the activities are practicing, repetition, receiving and sending messages: getting the idea quickly, analyzing and reasoning, creating structure for input and output, summarizing, translating, using L1. It means that the result of this study is quite different from the previous study conducted by Ramos (2017) in which this study only found that the visually impaired students used cognitive strategy, by conducting several activities like practicing, repetition, summarizing, and translating.…”
Section: Findings and Discussionsupporting
confidence: 84%
“…The third one is social strategies which is including asking questions to others about what that they do not know and also cooperate with others to know something that they do not understand (Oxford, 1990). Ramos (2017) explained that during their EFL learning process, the visually impaired students are practicing, doing repetition, getting idea quickly, analyzing and reasoning, creating structure for input and output, summarizing, and translating English by their first language (Ramos, 2017). Those activities are categorized as cognitive strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations